Democracy and anti-democracy in early modern England, 1603-1689 - Cuttica, Cesare; Peltonen, Markku (History of European political and constitutional thought, 2019)
This cross-disciplinary collection of essays examines - for the first time and in detail - the variegated notions of democracy put forward in seventeenth-century England. It thus shows that democracy was widely explored and debated at the time; that anti-democratic currents and themes have a long history; that the seventeenth century is the first period in English history where we nonetheless find positive views of democracy; and that whether early-modern writers criticised or advocated it, these discussions were important for the subsequent development of the concept and practice 'democracy'. By offering a new historical account of such development, the book provides an innovative exploration of an important but overlooked topic whose relevance is all the more considerable in today's political debates, civic conversation, academic arguments and media talk. Contributors include Camilla Boisen, Alan Cromartie, Cesare Cuttica, Hannah Dawson, Martin Dzelzainis, Rachel Foxley, Matthew Growhoski, Rachel Hammersley, Peter Lake, Gaby Mahlberg, Markku Peltonen, Edward Vallance, and John West.